Otter Creek and Springside, Pottawatomie County - Stratton, Jacob (Kansas State University, The Chapman Center for Rural Studies, 2016)
Otter Lake and Springside were two post villages in northwestern Pottawatomie County, Kansas locked in competition for hinterland resources and community perseverance along the Central Line of the Union Pacific Railroad. These twin towns struggled to survive. This study tracks this story between 1870 and 1920. This study uses period appropriate newspapers, Polk business directories, and books on Pottawatomie and Marshall counties. The main conclusion of the study finds the failure of Otter Lake and eventually Springside.
Jacob Stratton, “Otter Creek and Springside, Pottawatomie County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/171.
Keywords: Otter Lake; Pottawatomie County; Marshall County; Fostoria; Spring Creek; Springside